Allelopathic effect of annoni grass extracts on Vachellia caven (Molina) Seigler & Ebinger germination and initial development - Mendes, Yago Luís Nóbrega; Binotto, Julia Savegnago; Quatrin, Marciéli; Brasil, Nicolas Gibran Marques; Bevilaqua, Daiane Balconi; Stefanello, Raquel; Vestena, Silvane (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Eragrostis plana Nees is one of the species with the greatest invasive potential in natural grassland areas in southern South America, due to its biological and ecological characteristics and the interactions it maintains with other plant species, especially native species. The aim of this study was to evaluate the allelopathic effect of Eragrostis plana on the germination of Vachellia caven (Molina) Seigler & Ebinger seeds. The experimental design was completely randomized with four replicates of 50 seeds per treatment. The seeds were placed on germitest paper containing aqueous extracts of E. plana in different concentrations (0, 25, 50, 75 and 100%) and placed in a controlled environment with 16 hours of light. It was observed that E. plana has a positive allelopathic effect on V. caven, stimulating the germination process and the initial development of the seedlings.